Birth order, educational attainment and earnings: an investigation using the PSID - Jasmin Kantarevic; Stéphane Mechoulan (Institute for the Study of Labor (IZA), 2005)
Whether siblings of specific birth order perform differently has been a longstanding open empirical question. We use the family tree structure of the PSID to examine two claims found in the literature: whether being early in the birth order implies a distinct educational advantage, and whether there exists, within large families, a pattern of falling then rising attainment with respect to birth order, to the point where it becomes best to be last-born. Drawing from OLS and family fixed effects estimations, we find that being first-born confers a significant educational advantage that persists when considering earnings; being last-born confers none.
Keywords: I2; J1; 330; birth order; family size; education; Kinder; Familie; Bildungsverhalten; Ethnische Gruppe; USA